UPAYA MENGOPTIMALISASI POTENSI WISATA KAWASAN EKS-STASIUN PURI SEBAGAI BENDA CAGAR BUDAYA DI KABUPATEN PATI - Ismiyatin, Laela; Sabardila, Atiqa (Universitas Negeri Malang, 2021)
Historical buildings in Indonesia have undergone many changes, either partially or completely. The purpose of the change itself is due to give an attractive impression and provide economic benefits for the government and individuals in the area around the historical building. The purpose of this study is to provide knowledge regarding the efforts made by the local government to optimize the tourism potential in the Puri Ex-Station area as cultural heritage objects in the district of pati. This research is a qualitative descriptive study using interview methods, documentation and historical participation which is used to describe the potential of the ex-station castle as well as building optimization efforts to obtain benefits that can be useful for all parties. The results of this study indicate a potential of a building that has been unused and neglected for a long time which provides potential as a cultural heritage object that can provide historical value to the people around pati which can be used as a tourist attraction at night which has aesthetic beauty for taking selfies. Efforts that must be made are forming networks, providing counseling, socializing the community, contributing energy to cultural heritage, providing information to one another, while the resulting impact is increasing harmony and synergy between the community and the government which causes an increase in the community's economy. Bangunan bersejarah di Indonesia sudah mengalami banyak perubahan, baik sebagian ataupun seluruhnya. Tujuan dari perubahan sendiri dikarenakan untuk memberikan kesan menarik dan memberikan keuntungan ekonomi bagi pemerintah maupun individu diwilayah sekitar bangunan bersejarah. Tujuan penelitian ini untuk memberikan pengetahuan perihal upaya yang dilakukan pemerintah setempat untuk mengoptimalisasi potensi wisata yang berada di kawasan Eks-Stasiun Puri sebagai benda cagar budaya yang ada di kabupaten pati. Penelitian ini merupakan penelitian deskriptif kualitatif yang menggunakan metode wawancra, dokumentasi serta historis partisipasi yang digunakan untuk penggambaran potensi Eks-stasiun puri serta upaya pengoptimalisasian bangunan untuk mendapatkan manfaat yang bisa berguna untuk semua pihak. Hasil penelitian ini menunjukan sebuah potensi yang dimiliki bangunan yang sudah lama tidak terpakai dan tidak terurus yang memberikan potensi sebagai benda cagar budaya yang bisa memberikan nilai sejarah untuk masyarakat sekitar pati yang bisa dijadikan sebagai objek wisata dimalam hari yang memiliki keindahan estetik untuk berswafoto. Upaya yang harus dilakukan yaitu membentuk jaringan, memberikan penyuluhan, melibartkan masyarakat, sumbangan tenaga untuk cagar budaya, saling memberikan informasi sedangkan dampak yang dihasilkan adalah meningkatkan kerukunan dan sinergi antara masyarakat dan pemerintah yang menyebabkan peningkatan ekonomi masyarakat.